Analisis Kinematika Jump Smash pada Olahraga Bolavoli dengan Pendekatan Dua Dimensi Gerak - Widiantari, Ni Luh Gde; Astrawan, I Putu; Widhiyanti, Komang Ayu Tri; Kresnayadi, I Putu Eri; Indrawathi, Ni Luh Putu; Bagia, I Made (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study investigated the influence of the jump smash technique (with and without approach) on the accuracy and kinematic parameters of volleyball players' movements, utilizing two-dimensional video analysis (Kinovea) on 12 club members. The kinematic analysis results showed significant differences in three key variables: jump height, external shoulder rotation, and backward trunk lean, where the jump smash technique with approach demonstrated superior values. Although the accuracy data indicated a higher average for the technique without approach (3.85 vs. 3.02), the study concluded that the jump smash technique with approach provided a more significant overall impact on both accuracy and changes in kinematic parameters in the players.volleyball club, when compared to the jump smash technique without a run-up.